TYPES OF GYMNASTICS AND THEIR DESCRIPTIONS - Seytbekova Zulfiya Reymbekovna (Proximus Journal Publishing, 2024)
The article discusses the training of sports gymnastics, its importance in human life, details the history and types of gymnastics
Keywords: Sports; gymnastics; body; strength